Elderly People in Dependency Status from Argentina: Classification proposal according to Severity Level based on Secondary Data - Monteverde, Malena; Pujol-Jover, María; Alemany, Ramón; Lopez-Casasnovas, Guillem (Población y Salud en Mesoamérica, 2017)
The magnitude of the population 65 years and over in dependency status (ie, people with long-term care need) in Argentina would be more than one million people. Given the great heterogeneity in the type and intensity of the aid required by individuals with long-term care need, it is essential to establish some criteria to classify those in homogeneous groups in terms of severity. Objective: This work aims to establish a methodology and objective criteria that allow the identification of homogeneous groups of people in dependency status on the basis of secondary (and limited) information. Methods: The method used is based on the Valuation Scale of Dependency Situation from Spain and on the application of the Classification Trees method under the rpart function of the R program. The main sources of information are the Survey on Disability, Personal Autonomy and Dependency Situations from Spain (EDAD, 2008) and the National Survey on Quality of Life of the Elderly from Argentina (ENCaViAM, 2012). Results: the model selected shows a high degree of adjustment suggesting that it is possible to estimate the distribution of the elderly population in dependency status according to their severity level in a reasonable way from a reduced group of variables. Conclusions: although the prevalence of dependency among the elderly would be higher in Argentina than in Spain, the relative importance of groups with greater severity would be lower in the first country (in Argentina).